A review of four decades of atmospheric trace gas measurements at Cape Point, South Africa. Issue 2 (4th May 2018) - Labuschagne, Casper; Kuyper, Brett; Brunke, Ernst-Günther; Mokolo, Thumeka; van der Spuy, Danie; Martin, Lynwill; Mbambalala, Ernst; Parker, Bhawoodien; Khan, M. Anwar H.; Davies-Coleman, Michael T.; Shallcross, Dudley E.; Joubert, Warren
Abstract : South Africa's Cape Point (CPT) trace gas observatory, operated by the South African Weather Service (SAWS), has been monitoring mole fractions (mol/vol) of ambient greenhouse gases (GHGs), e.g. carbon dioxide (CO2 ), methane (CH4 ), nitrous oxide (N2 O), and selected halocarbons (CFCs and CCl4 ) since the late 1970s. In addition, the Cape Point trace gas observatory boasts the longest atmospheric carbon monoxide (CO) dataset continuously from 1977 in the Southern Hemisphere (SH). Instruments for the measurement of radiation and other selected gases, such as ozone (O3 ), have gradually been added since the inception of measurements. The year 1995 heralded a milestone when the Cape Point observatory became part of the World Meteorological Organization's (WMO) Global Atmosphere Watch (GAW) programme. Besides supplying data to the World Data Centres, it also supports the local database, South African Air Quality Information System (SAAQIS). These affiliations, which require strict measurement protocols, make the Cape Point data records available within the global data centres. Due to Cape Point's location in a mostly pristine marine environment and its proximity to the Southern Ocean, measurements are highly valued in the United Nations Environment Programme (UNEP)/WMO Ozone and IPCC Climate Assessments and serve as a bellwether for regional changes in southern African atmospheric composition. A review of selected climate change relevant trace gas measurements acquired at Cape Point is presented here.